Evidence of changes in sexual behaviours among male factory workers in Ethiopia. - Mekonnen, Y; Sanders, E; Aklilu, M; Tsegaye, A; Rinke de Wit, T; Schaap, A; Wolday, D; Geskus, R; Coutinho, R; Fontanet, A (2003)
OBJECTIVE: To assess changes in sexual behaviours among male factory workers in Ethiopia. DESIGN: Open cohort studies in two factories near Addis Ababa. DATA AND METHODS: At intake and biannual follow-up visits, data were collected on sexual behaviours including casual sex, sex with commercial sex workers (CSW), condom use, and history of sexually transmitted diseases (STDs) as indicated by genital discharge and genital ulcer. Health education, HIV testing, and counselling were offered to all participants. RESULTS: Between February 1997 and December 1999, 1124 males were enrolled in the two cohort studies. At intake, the prevalence of casual sex in the past year, sex with CSWs, condom use with the last casual partner, history of genital discharge in the past 5 years, and history of genital ulcer in the past 5 years were 9.7, 43.4, 38.8 (Akaki site only), 10.6 and 2.1%, respectively. At the Wonji site, the intake prevalence of casual sex, sex with CSW, and history of genital discharge decreased significantly by calendar year between 1997 and 1999. At both sites combined, between the first and the fourth follow-up visits, there was a decline in the proportion of males reporting recent casual sex (from 17.5 to 3.5%, < 0.001), sex with CSWs (from 11.2 to 0.75%, < 0.001), and genital discharge (from 2.1 to 0.6%, = 0.004). CONCLUSION: There was a decline over time in risky sexual behaviours reported by cohort participants. Part of this decline occurred independently of cohort interventions.